Workload and work engagement among nurses in public hospitals: moderating role of religious spirituality - Zahrah, Novia; Aziz, Azelin; Abdul Hamid, Siti Norasyikin (2019)
The aim of this study is to investigate the moderating role of religious spirituality on the relationship between workload and work engagement among nurses in Malaysia Public Hospitals. A quantitative correlational research and questionnaire method is applied in this study. Sample sizes of 364 that consist of Staff Nurses were selected through multistage sampling. SPSS and Smart-PLS were utilized as the analytical tools of this study. The assessment of the inner model (measurement model) and the assessment of the outer model (structural model) were conducted to test the hypothesis. The result shows that it supports the relationship between workload and work engagement. But it shows that religious spirituality has no moderating effects on the relationship between workload and work engagement. Future studies might have significant result relating to moderating role of religious spirituality in mitigating the effect of workload on work engagement. By understanding the relationship among the constructs in this study, healthcare institutions could improve work engagement level of nurses in spite of the high workload. The management also could coordinates and provides nurses a training relating to religious spirituality to facilitate nurses to be more resilient in dealing with job complexity of nursing tasks and high job demands, which in turn it will enhances the nurses’ work engagement level.